Analisi Strategi Guru Kelas V dalam Pembelajaran IPA di Era Pandemi Covid-19 SD Gugus V Kecamatan Sibulue Kabupaten Bone - Muliadi Muliadi; Sudarto Sudarto; Megawati Megawati (JPPSD: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2022)
The problem in this study is to find out the learning strategies of fifth grade teachers in the era of the covid-19 pandemic in Elementary School cluster V, Sibulue District. This research is a type of descriptive qualitative research that aims to: 1) find out the strategies of fifth grade elementary school teachers in cluster V, Sibulue District, Bone Regency in learning science in the era of the covid-19 pandemic, 2). knowing the obstacles in implementing strategies in SD cluster V, Sibulue District, Bone in learning science in the era of the covid-19 pandemic. Data was collected by means of questionnaires and interviews. Data analysis techniques are data reduction, data display, conclusion drawing. The results of this study indicate that the strategies used by teachers in science learning are online and offline learning strategies. The teacher's obstacles during the implementation of learning strategies are not all students have cellphones, the quality of the internet network is weak, they do not have sufficient internet quota and there are differences in the character of each student.